Eksperimen Pembelajaran Matematika Dengan Strategi Relating, Experiencing, Applying, Cooperating And Transferring (REACT) Terhadap Hasil Belajar Ditinjau Dari Minat Belajar Pada Siswa Kelas VIII Semester Gasal SMP N 1 Wonosari Tahun 2015/2016 - Hastuti, Erna Widiyah (2016)
The result of mathematics learning is very important to measure the students' competence towards the learning materials which has been discussed. Strategies are needed in order to improve the result of learning. The strategies are Relating, Experiencing, Applying, Cooperating, Transferring(REACT). Besides, the students' interest also influence towards the learning result. The research is conducted to know : (1) the contribution of REACT strategy toward the result of mathematics learning, (2) the contribution of students' interest towards the result of mathematics learning, (3) interaction between REACT strategy and students' interest towards the result of mathematics learning. The research population is the students of VIII from SMP N 1 Wonosari in the year 2015/2016. There are two classes used as sampling which each consists of 31 students. Class VIIIC as the experimental class using REACT strategy and class VIIIA as the control using expository strategy. The technique of sampling is random sampling. The technique of collecting data are test, inquiry, and documentation. The technique of analizing data by two ways variance analysis i.e. different cells. The research result at  = 0,05shows that: (1) there is contribution REACT strategy towards the result of mathematics learning i.e. Fobs = 8,670917543 > F = 4,01; (2) there is a contribution of students' interest towards the result of mathematics learning i.e.Fobs = 5,191398373 > F = 3,16; (3) there is aninteraction between REACT strategy and students' interest towards the result of mathematics learning i.e.Fobs = 4,343721811 > F = 3,16.